Comparison of the effects of dietary flavonoids and statins on lipopolysaccharide-induced vascular inflammation - Alshalmani, Salmin Khalid (2011)
Numerous epidemiological studies indicate that flavonoid intake as part of a balanced diet confers beneficial health effects in man, including improved cardiovascular function, reduced incidence of cancer and amelioration of symptoms associated with inflammatory disorders (Boots et al., 2008). A recent area of interest that may be fruitful is the study of anti-inflammatory effects of flavonoids in combination with statins.